Epicardial fat tissue, a hidden enemy against the early recovery of left ventricular systolic function after transcatheter aortic valve implantation - Helen S. Anwar; Pilar Lopez Santi; Magdy Algowhary; Mohamed Aboel-Kassem F. Abdelmegid; Hatem A. Helmy; J. Wouter Jukema; Nina Ajmone Marsan; Frank Van Der Kley (International Journal of Cardiology: Heart & Vasculature)
Background: Epicardial fat tissue (EFT) is an active organ that can affect cardiac function and structure through endocrine, paracrine, and proinflammatory mechanisms. We hypothesized that greater thickness of EFT may harm the recovery of left ventricular (LV) systolic function in patients with severe aortic stenosis (AS) and reduced LV ejection fraction (EF ≤ 50 %) undergoing transcatheter aortic valve implantation (TAVI). Methods: A sixty six patients with severe AS and 20 % ≥ LVEF ≤ 50 % who underwent TAVI were included. Patients were categorized into two groups based on LV systolic function recovery 30 days after TAVI defined by ≥ 20 % relative increase in LV Global longitudinal strain (GLS) from baseline. EFT was determined by ECG-gated contrast-enhanced multidetector computed tomography (MDCT). Results: Forty-five patients (68.0 %) showed LV systolic function recovery. EFT showed no significant correlation with the baseline LV-GLS but was associated with less likelihood of LV systolic function recovery (OR 0.7, 95 % CI 0.50 – 0.98, P = 0.04). In the multivariate analysis, higher LVMI (OR 1.05, 95 % CI 1.00–1.10, P = 0.02), lower LV-GLS (OR 0.55, 95 % CI 0.40–0.82, P = 0.002), and thinner EFT (OR 0.38, 95 % CI 0.20–0.73, P = 0.003) were independently associated with LV systolic function recovery after TAVI. Conclusion: EFT extent is associated with LV systolic function recovery in AS patients with impaired LVEF undergoing TAVI and therefore may help in risk stratification and management of these patients.